Comprehensive Physiology 2019
DOI: 10.1002/cphy.c180035
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Peptides—Gastrin and Somatostatin

Abstract: Gastric acid secretion (i) facilitates digestion of protein as well as absorption of micronutrients and certain medications, (ii) kills ingested microorganisms, including Helicobacter pylori, and (iii) prevents bacterial overgrowth and enteric infection. The principal regulators of acid secretion are the gastric peptides gastrin and somatostatin. Gastrin, the major hormonal stimulant for acid secretion, is synthesized in pyloric mucosal G cells as a 101-amino acid precursor (preprogastrin) that is processed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 476 publications
0
25
0
Order By: Relevance
“…[26][27][28] Also, shorter (gastrin-14 and gastrin-6) as well as longer gastrins (gastrin-71) are synthesized and secreted, but only in small quantities. [29][30][31] The synthesis of gastrin is cell-specific (for reviews, see Rehfeld, 1 Rehfeld et al, 32 and Schubert and Rehfeld 33 ) Therefore, in the present context, it is noteworthy that the specific gastrin-producing cells in the foetal and neonatal pancreatic islets synthesize mainly O-sulphated gastrin-17. 4,34 The sulphation, however, does not change the insulinotropic activity of gastrin.…”
mentioning
confidence: 80%
“…[26][27][28] Also, shorter (gastrin-14 and gastrin-6) as well as longer gastrins (gastrin-71) are synthesized and secreted, but only in small quantities. [29][30][31] The synthesis of gastrin is cell-specific (for reviews, see Rehfeld, 1 Rehfeld et al, 32 and Schubert and Rehfeld 33 ) Therefore, in the present context, it is noteworthy that the specific gastrin-producing cells in the foetal and neonatal pancreatic islets synthesize mainly O-sulphated gastrin-17. 4,34 The sulphation, however, does not change the insulinotropic activity of gastrin.…”
mentioning
confidence: 80%
“…GAS was secreted by the gastrin-releasing enteroendocrine cells (G-cells), which were found in the antrum and duodenum and regulated by central and peripheral nerves. e primary physiological function of gastrin is the stimulation of gastric acid secretion [30]; in addition, it can accelerate the gastric electric rhythm and promote gastric emptying [31]. Some experiments have indicated that rats with gastrointestinal disorders cause decrease in GAS in the plasma, gastrointestinal fluids, duodenum, gastric antrum, and tissues of the hypothalamus [32].…”
Section: Discussionmentioning
confidence: 99%
“…During the phase of digestion, the inhibitory effect of somatostatin on gastrin maintains gastric acid secretion at a relatively low level. During food intake, the inhibition of somatostatin by activating cholinergic neurons can maximize the secretion of gastric acid, while also directly stimulating G-cells [30]. VIP is an important Evidence-Based Complementary and Alternative Medicine gastrointestinal hormone and is widely distributed in the gastrointestinal tract and central nervous system, regulated to ion secretion, nutrient absorption, gut motility, glycemic control, carcinogenesis, immune responses, and circadian rhythms [37].…”
Section: Discussionmentioning
confidence: 99%
“…90% of SST cells in the GI tract are endocrine cells, while 10% are neurons in the ENS (5). SST-SSTRs have an inhibition effect on the physiological functions of digestion and absorption in the GI system (8,9). SST release from the pituitary and SST in circulatory blood could modulate GI function via its receptors.…”
Section: Sst and Sstrs In Gastrointestinal Systemmentioning
confidence: 99%
“…There are various SST-endocrine-cells embedded in the GI tract, which release gastrointestinal hormones to regulate GI function, such as SST producing-D cells from the stomach, intestine, and pancreas. SST in the GI system is involved in the inhibition of secretory activity and intestinal motility, blood flow, inflammation response, conduction of pain and sensation, and modulation of the release of hormone factors and other neurotransmitters, while SST-SSTRs mediate the release of gastric juice, intestinal juice, gastric acid, and other hormones via other endocrine factors (7)(8)(9). In addition, SST-SSTRs in non-GI tracts also are involved in digestion and absorption functions, such as the pancreas, liver, and gallbladder (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%